Prevalence and outcomes of neonatal anaemia in university of medical sciences teaching hospital, Akure - Oluwafemi, Rosena O.; Bello, Emmanuel O.; Oluwafemi, Toluwani M.; Onoja, Raymond E.; Adeleye, Oluwafemi J. (International Journal of Research in Medical Sciences, 2025)
Background: Neonatal anaemia is a public health problem associated with short- and long-term morbidities. It can lead to death if not immediately treated or impairment in brain maturation and development, tissue hypoxia and stunted growth eventually. The aim and objectives of the study is to determine prevalence, associated factors and immediate outcomes of neonatal anaemia in the University of Medical Sciences Teaching Hospital (UNIMEDTH), Akure. Methods: This was a retrospective review of the medical records of all consecutive neonatal admissions in the neonatal intensive care unit (NICU) of the hospital over a nine-month period. At admission, peripheral blood sample was collected routinely within one hour of life for Packed Cell Volume at the side laboratory. Other relevant data were extracted from the case files and documented in the excel sheet which were exported unto the Statistical Package for Social Sciences (SPSS) version 25.0 for analysis. Results: Of the 145 babies studied, 30 were anaemic with one mortality; 132 (91.1%) of them were admitted within 24 hours of life, the commonest morbidity among them was prematurity, ABO incompatibility, neonatal sepsis and anaemia. Caesarean delivery, very low birth weight, longer duration on admission, prematurity and lower gestational age were significantly associated with neonatal anaemia while gender was not. Conclusions: The prevalence of anaemia among neonates in UNIMEDTH was 20.7%. The mortality was 3.3% and the only death occurred among babies with feto-placental transfusion.